Integrating immunotherapy with conventional treatment regime for breast cancer patients- an amalgamation of armamentarium - Nandi, Deeptashree; Sharma, Dipali (Frontiers in Immunology, 2024)
Immunotherapy stands as the frontrunner in treatment strategies imparting efficient remission in various types of cancer. In fact, emerging breakthroughs with immune checkpoint inhibitors (ICI) in a spectrum of cancers have evoked interest in research related to the potential effects of immunotherapy in breast cancer patients. A major challenge with breast cancer is the molecular heterogeneity that limits the efficacy of many therapeutic regimes. Clinical trials have shown favorable clinical outcomes with immunotherapeutic options in some subtypes of breast cancer. However, ICI monotherapy may not be sufficient for all breast cancer patients, emphasizing the need for combinatorial approaches. Ongoing research is focused on untangling the interplay of ICI with established as well as novel anticancer therapeutic regimens in preclinical models of breast cancer. Our review will analyze the existing research regarding the mechanisms and clinical impact of immunotherapy for the treatment of breast cancer. We shall evaluate the role of immune cell modulation for improved therapeutic response in breast cancer patients. This review will provide collated evidences about the current clinical trials that are testing out the implications of immunotherapy in conjunction with traditional treatment modalities in breast cancer and summarize the potential future research directions in the field. In addition, we shall underline the recent findings related to microbiota modulation as a key regulator of immune therapy response in cancer patients and its plausible applications in breast cancer.